Data Processor to Estimate Raw Meal Dosing for Cement Manufacture - Pompilla Cáceres, Nidia (2022)
In the cement industry, the dosing of raw materials is an important stage in which mixtures called cement raw materials are obtained. The chemical and mineralogical composition of the clinker and the type of cement to be produced will depend on the content of these raw mixtures. Empirical calculation methods are usually used to determine the appropriate raw meal proportions; in practice, application of such methods is difficult due to their complexity and the limited use of conventional programs. In this applied research, a data processor was designed to estimate the chemical composition of raw meal. The methodology involved the development of equations, the design of the program and its validation. Its functionality, effectiveness and interaction with the user were verified based on the results, obtaining a processor that adequately manage data related to raw materials and cement type, and obtains very acceptable results.